2014
DOI: 10.1016/j.jagp.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Circadian Activity Rhythm Disturbances in Community-Dwelling Older Women

Abstract: Objectives Aging is associated with changes in circadian rhythms. Current evidence supports a role for circadian rhythms in the pathophysiology of depression. However, little is known about the relationship between depressive symptoms and circadian activity rhythms in older adults. We examined this association in community-dwelling older women. Methods We performed a cross-sectional analysis of 3,020 women (mean age: 83.55 ± 3.79 years) enrolled in the Study of Osteoporotic Fractures. Depressive symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 50 publications
4
50
1
Order By: Relevance
“…Among community-dwelling older women, Maglione et al (6) found that having low RAR amplitude, mesor, pseudo F-statistic, and earlier evening settling all marked prevalent depressive symptoms independent of health status covariates. Standardized amplitude and having a later-up mesor were also associated with depression symptoms, but these associations were attenuated by adjustments for covariates.…”
Section: Evidence For Rars As a Marker Of Depressionmentioning
confidence: 99%
“…Among community-dwelling older women, Maglione et al (6) found that having low RAR amplitude, mesor, pseudo F-statistic, and earlier evening settling all marked prevalent depressive symptoms independent of health status covariates. Standardized amplitude and having a later-up mesor were also associated with depression symptoms, but these associations were attenuated by adjustments for covariates.…”
Section: Evidence For Rars As a Marker Of Depressionmentioning
confidence: 99%
“…Activity rhythm disturbances are associated with depressed mood (Luik, Zuurbier et al, 2013; Maglione, Ancoli-Israel et al, 2013; Robillard, Naismith et al, 2014; Luik, Zuurbier et al, 2015). These prior studies have identified particular activity rhythm characteristics (such as rhythm height, robustness, or timing) linked to depression.…”
mentioning
confidence: 99%
“…Rhythm amplitude, robustness and timing of peak activity have also been shown to predict incident dementia among older women 9 . A recent cross-sectional study demonstrated that older women with greater levels of depressive symptoms were more likely to have circadian rhythm disturbances, specifically lower amplitude and less robust CARs 10 . No previous research has reported cross-sectional associations of CARs and depression in older men.…”
mentioning
confidence: 99%